Генетическое разнообразие, происхождение и закономерности распространения полиплоидных щиповок (Cypriniformes, Cobitidae, Cobitis) в пределах Украины - Межжерин, С.В.; Павленко, Л.И. (Цитология и генетика, 2010)
В водоемах Украины обнаружено 16 из 28 возможных биотипов C. elongatoides – taenia s. lato (С. taenia, C. tanaitica, C. species-1). Также выявлены биотипы предположительно C. aff. melanoleuca – tanaitica. Доля полиплоидов в поселениях щиповок в среднем составила 65 %, самцов среди них – менее 1 %, причем в равном соотношении среди три- и тетраплоидов. Вызывает интерес отсутствие амфидиплоидии, а также встречи особей с рекомбинированным генотипом и аномальными электрофоретическими спектрами, частота которых местами значительна. Выделяются два очага образования полиплоидных биотипов: южный (Низовья Дуная) и северный (Верховья Дуная, Одер, Рейн). В последнем наряду с C. elongatoides и C. tanaitica в образовании полиплоидов принимает участие С. taenia и С. species-1– вид, характерный для водоемов северо-запада Украины. Установлено, что биотипы (C. 2(3) elongatoides – tanaitica, C. elongatoides – 2 (3) tanaitica) по сравнению биотипами, в геном которых входит хромосомный набор С. taenia, ограничены в своем распространении на восток. Причиной является гибридизация самок этих биотипов с самцами С. taenia, сопровождающаяся генетической нестабильностью и пониженной жизнеспособностью потомства. У водоймах України знайдено 16 з 28 можливих біотипів C. elongatoides – taenia s. lato (С. taenia, C. tanaitica, C. species-1). Також виявлено біотипи імовірно C. aff. melanoleuca – tanaitica. Частка поліплоїдів у поселеннях щиповок в середньому становить 65 %, самців серед них – менше 1 %, причому у рівному співвідношенні серед три- и тетраплоїдів. Викликає інтерес відсутність амфідиплоїдії, а також зустрічі особин з рекомбінованим генотипом і аномальними електрофоретичними спектрами, частка яких місцями значна. Виділяються два центри утворення поліплоїдних біотипів: південний (Низов’я Дунаю) і північний (Верхів’я Дунаю, Одер, Рейн). В останньому випадку поряд з C. elongatoides і C. tanaitica в утворенні поліплоїдів приймає участь С. taenia и С. species-1 – вид, характерний для водойм північного заходу України. Встановлено, що біотипи (C. 2 (3) elongatoides – tanaitica, C. elongatoides – 2 (3) tanaitica) у порівнянні з біотипами, до геному яких входить хромосомний набір С. taenia, обмежені в своєму поширенні на схід. Причиною є гібридизація самок цих біотипів з самцями С. taenia, що супроводжується генетичною нестабільністю і зниженою життєздатністю нащадків. Only 16 biotypes from 28 possible ones, which could be generated during hybridization of C. elongatoides, on the one hand, and representatives of superspecies C. taenia s. lato (С. taenia, C. tanaitica, C. species-1), on the other hand, were discovered in water areas of Ukraine. Furthermore, two biotypes, presumably C. aff. melanoleuca – tanaitica, were discovered in the north-western regions. Polyploids have compounded 65 % of investigated individuals of Сobitis genus, the average quantity of males has compounded less than 1 % and it was equal among triploids and tetraploids. Absence of amphidiploids and also lack of sufficiently large number of individuals with recombined genotype and abnormal electrophoretic spectra should be stressed. Two loci of polyploid biotypes formation are marked out: southern (the Lower Danube) and northern (the Upper Danube, Оder and Rhine). С. taenia and non-specified С. species, typical of the north-western basins of Ukraine, participate in formation of polyploids in the last mentioned river alongside with C. elongatoides and C. tanaitica. It is established that in spite of clearly evident expansion capacity, so-called southern biotypes (C. 2 (3) elongatoides – tanaitica, C. elongatoides – 2 (3) tanaitica) in comparison with the northern ones, which genome includes chromosomal complement С. taenia or С. species1, are sharply limited in their spread to the East. The reason of such a situation is unbalanced gynogenetic crossing between females of the southern biotypes and С. taenia males, accompanied by introgressions, genetic instability and reduced posterity viability.